EXPANDED THE PRODUCTION EFFECTIVENESS THROUGH PRODUCTION PLANNING, RAW MATERIAL CONTROL, SCHEDULE CONTROL AND PRODUCTION CONTROL AT PT. LPA - Afthon Kumbara; Agustinus Hariadi DP (Dinasti International Journal of Education Management And Social Science, 2021)
PT. LPA is one of textile manufacturing company who is still doing the production process by woven fabrics (Weaving) and finishing fabrics (Printing, Dyeing and White). The problems that are often faced by PT. LPA is the completion time of production which is still not according to the targets that have been planned, then the production effectiveness would not be achieved so with the suitability of orders or quality which has not been met with expectation. This research aims to find out the impact of production planning on raw material control, schedule control and production control as well as the impact from raw material control to production effectiveness, schedule control affect on production effectiveness and production control affect on production effectiveness. Questionnaire data analysis which involves 65 respondents, those employees from PT. LPA then the data would be processed through validity and reliability test using the PLS-SEM analysis method. So the results that obtained from this research were production planning had a positive and significant impact on raw material control, production planning had a positive and significant impact on schedule control, production planning had a positive and significant impact on production control, raw material control had a positive and significant impact on production effectiveness, schedule control had a positive and significant impact on production effectiveness, production control had a positive and significant impact on production effectiveness.